Upaya Meningkatkan Kemampuan Perilaku Prososial Pada Anak Usia 5-6 Tahun Melalui Permainan Rubber Band Relay Di TKQ Miftahul Hidayah - Safitri, Ely; Syafrida, Rina; Siti Aisyah, Dewi (Jurnal Ilmu Pendidikan Islam, 2025)
Prosocial behavior is the basis of development that children must have, forms of prosocial behavior that must be instilled from early childhood, namely sharing, cooperation and empathy. This research aims to determine the prosocial behavior of children aged 5-6 years at TKQ Miftahul Hidayah. This classroom action research method uses the Kemmis and Mc Taggart model which is carried out in two cycles. The first cycle involved 6 meetings, while the second cycle only involved 5 meetings. This research involved 16 children, consisting of 9 boys and 7 girls. The data collection method in this study involved observing children's abilities in increasing prosocial behavior, observing teacher and student activities and recording the findings. In this research, the data analysis method involves the use of descriptive qualitative techniques along with basic statistical calculations. This research shows that using the rubber band relay game can improve children's prosocial behavior. In the first cycle, 57.28% of children were able to share, cooperate, help and empathize. In the second cycle, it showed an increase of 90,81%. So, using the rubber band relay game method, it can help improve children's prosocial behavior.